Social preferences across subject pools: Students vs. general population - Thomas Epper; Julien Senn; Ernst Fehr (University of Zurich, Department of Economics, 2024)
The empirical evidence on the existence of social preferences-or lack thereof-is predominantly based on student samples. Yet, knowledge about whether these findings can be extended to the general population is still scarce. In this paper, we compare the distribution of social preferences in a student and in a representative general population sample. Using descriptive analysis and a rigorous clustering approach, we show that the distribution of the general population's social preferences fundamentally differs from the students' distribution. In the general population, three types emerge: an inequality averse, an altruistic, and a selfish type. In contrast, only the altruistic and the selfish types emerge in the student population. We show that differences in age and education are likely to explain these results. Younger and more educated individuals-which typically characterize students-not only tend to have lower degrees of other-regardingness but this reduction in other-regardingness radically reduces the share of inequality aversion among students. Differences in income, however, do not seem to affect social preferences. We corroborate our findings by examining nine further data sets that lead to a similar conclusion: students are far less inequality averse than the general population. These findings are important in view of the fact that almost all applications of social preference ideas involve the general population.
Keywords: C80; C90; D30; D63; 330; Social Preferences; Altruism; Inequality Aversion; Preference Heterogeneity; Subject pools; Sample Selection